2014
DOI: 10.1038/cgt.2014.60
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN gene delivery suppresses regulatory T cells within tumors

Abstract: Type I interferon (IFN) is a pleiotropic cytokine regulating the cancer cell death and immune response. IFN-α can, as we have also reported, effectively induce an antitumor immunity by the activation of tumor-specific T cells and maturation of dendritic cells in various animal models. Unknown, however, is how the type I IFN alters the immunotolerant microenvironment in the tumors. Here, we found that intratumoral IFN-α gene transfer significantly decreased the frequency of regulatory T cells (Tregs) per CD4(+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Among them, pDCs are the major IFN-α-producing cells triggered by TLR7/9 signaling. IFN-α, in addition to its direct killing effect on tumor cells, induces tumor immunity by activating immune cells, including cytotoxic T lymphocytes, natural killer cells, and innate lymphoid cells (26)(27)(28), and by negatively regulating immune suppressive cells such as MDSCs (29) and Tregs (30). Our results showed that CpG-activated pDCs directly killed MM cells by secreting IFN-α in vitro, which may suggest the physiological function of pDCs in tumor immune surveillance.…”
Section: Discussionmentioning
confidence: 55%
“…Among them, pDCs are the major IFN-α-producing cells triggered by TLR7/9 signaling. IFN-α, in addition to its direct killing effect on tumor cells, induces tumor immunity by activating immune cells, including cytotoxic T lymphocytes, natural killer cells, and innate lymphoid cells (26)(27)(28), and by negatively regulating immune suppressive cells such as MDSCs (29) and Tregs (30). Our results showed that CpG-activated pDCs directly killed MM cells by secreting IFN-α in vitro, which may suggest the physiological function of pDCs in tumor immune surveillance.…”
Section: Discussionmentioning
confidence: 55%
“…TGF-β controls the development, differentiation, and function of Tregs (27) (NES = 1.7, P < 0.05), which further validates our model. Deletion of Tregs can lead to systemic inflammation (28,29), confirming their role in controlling inflammatory processes driven by type I IFNs (30,31). IFN-stimulated genes (ISGs) were upregulated in INRs, and overall, this was inversely associated with Treg frequencies in cycling memory CD4 + T cells (NES = -1.4, P < 0.05) ( Figure 3D).…”
Section: Introductionmentioning
confidence: 71%
“…The design and management of IFNbased therapies should take into account the sequential effects of a rapid actT reg decline and late Th1-like T reg depletion, which may reveal favorable or unfavorable consequences, depending on the context. For instance, they may result in favorable consequences in tumors, possibly by quickly restoring anti-tumor immune responses (owing to rapid actT reg decline), as well as by limiting chronic inflammation (owing to late Th1-like T reg depletion)data that may explain the beneficial effects of IFN-based tumor gene therapy in experimental tumor models [46,47]. Conversely, acute actT reg depletion that promptly occurs following IFN-a exposure may prevail and be detrimental in the case of some autoimmune disorders, such as systemic lupus erythematosus, in which recent preliminary evidence showed beneficial therapeutic effects of anti-IFN-a reagents [48].…”
Section: Discussionmentioning
confidence: 99%